Revision : Art Programmes of European Television Stations. - Beeren, W.A.L.; Bertheux, Maarten; von Bonin, Wibke; Bódy, Vera; Dercon, Chris; Fagone, Vittorio; Fallaux, Emile; Fargier, Jean-Paul; Gassert, Siegmar; Grundmann, Heidi; Herzogenrath, Wulf; Mignot, Dorine; et al. (Amsterdam : Stedelijk Museum Amsterdam, 1987)
Kriesche, Richard ; Hintze, Ida ; Weibel, Peter ; Bechtold, Gottfried ; Rainer, Arnulf ; Davis, Douglas ; Zykan, Otto M. ; Gruber, N. ; Scheffknecht, Romana ; Drupsteen, Jaap ; Graf, Inge ; X, Robert Adrian ; Pezold, Friederike ; Scheffknecht, David ; Paik, Nam June ; Abramovic, Marina & Ulay ; Casinière, Joëlle de la ; Riga, Jean-Claude ; André, Marie ; Rombouts, Rob ; Cornelis, Jef ; Decostere, Stefaan ; Dercon, Chris ; Averty, Jean-Christophe ; Jaffrenou, Michel ; Bousquet, Patrick ; Mieville, Jean-Luc Godard & Anne-Marie ; Kuntzel, Thierry ; Grandrieux, Philippe ; Jung, Jean-François ; Fargier, Jean-Paul ; Cahen, Robert ; Longuet, Alain ; Huter, Stephane ; Jaffrenou, Michel ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Piene, Otto ; Tambellini, Aldo ; Emmerling, Hans ; Mack, Heinz ; Wiehn, Karl ; Lehmstedt, Dietrich ; Willikens, Ben ; Eichel, Manfred ; Ottinger, Ulrike ; Dreher, Christoph ; Malki, Ellen El ; Stefanowski, Michael ; Anding, Volker ; Wentscher, Herbert ; Bruch, Klaus vom ; Dali, Salvador ; van der Keuken, Johan ; de By, Henk ; Schippers, Wim T. ; de Ridder, Willem ; Rooyens, Bob ; Mechanicus, Philip ; Keller, Hans ; Ivens, Joris ; Schouten, Lydia ; LeGué, Raymond ; Drupsteen, Jaap ; Otth, Jean ; Minkoff, Gérald ; Olesen, Muriel ; Marthaler, Adrian ; Edelstein, Simon ; Klenk, André ; Bosman, Fred ; Clarke, Kenneth ; Berger, John ; Hall, David ; Read, John ; Greenaway, Peter
Revision : Art Programmes of European Television Stations, Stedelijk Museum Amsterdam, 04.09 - 18.10.1987
Engels
boek